Metode Tafsīr Bāṭinī Syī’ah: Sebuah Telaah Kritis - Muhammad Abdul Malik Al-Furqon; Muhammad Taqiyuddin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Method of Tafsīr Bāṭinī Syī’ah: A Critical StudyGiven the urgency that the Bāṭinī’s Tafsir (interpretation) it self is classified by some scholars as the Sufistic model of Isyārī's interpretation which puts forward metaphorical exegesis, thus, its position is controversial and needs to be explained. In fact, Bāṭinī’s interpretation is widely used by the Shi'ah school. The methodology of Bāṭinī’s interpretation in Syī'ah is identical to their aqīdah. This study, using the literature research model, involved an object in the form of Syī'ah literature simply referred to as an authoritative source; especially from the Islamic scholars who are mu'tabar. The data were analyzed descriptively and in a comparative analysis following a critical analysis of the empirical literature; namely the narrative model. Thus, the narrative of Bāṭinī Shī'ah's interpretation model was revealed, to be juxtaposed with several Tafsīr works having been rooted in the Sunni tradition as a relevant source to explain the position of Bāṭinī's interpretation and the ideological influence surrounding and underlying its emergence. This study found that the Bāṭinī’s interpretation was identical to the transition of the meaning of the verse al-Qur'ān from its zāāir to its bāṭin; by highlighting several specific patterns oriented towards strengthening one of the pillars of the Shī'ah teachings itself, namely the Imāmah.